A rare case of urothelial carcinoma arising in mature cystic teratoma - Maurya, Nitesh R.; C. Bhavsar, Urvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Mature cystic teratoma is a common benign adnexal tumour in females. It is composed of all the three germ layers (mesoderm, endoderm and ectoderm). Malignant transformation in a mature cystic teratoma of the ovary is rare, occurring in only 1-2% of cases. The most common malignancy is squamous cell carcinoma, which consists of about 80% of malignant transformations. Here we report malignant transformation of MCT in a 74year old post-menopausal female. Grossly the ovary was large cystic occupying the entire abdomen. Trial dissection was done and only 50% of the mass could be dissected due to gross adhesions. HPE reported as urothelial carcinoma in mature cystic teratoma. MCT is easily diagnosed via sonography, but malignant transformation is difficult to identify before surgery. For patients with malignant transformation, squamous cell carcinoma is the most common malignancy arising from MCT, and accounts for 80% of all cases. Other malignancies, such as adenocarcinomas, sarcomas or malignant melanomas have been reported; however, urothelial carcinoma arising from MCT is rare.